Peningkatan Kualitas Pakan Ternak Berbasis Teknologi Tepat Guna Mesin Pencacah Rumput di Desa Sambigede - Sujito, Sujito; Kusuma, Fuad Indra; Sumarli, Sumarli; Witjoro, Agung; Thoriq Bachtiar Y. E (Yayasan Literasi Sains Indonesia, 2023)
In community service activities, the State University of Malang is now partnering with Sambigede Village, Sumberpucung District, Malang Regency, East Java. Sambigede Situated within the beautiful landscape of the region, this village is characterized by its serene environment and close-knit community. With a population primarily engaged in agriculture and small-scale enterprises, Sambigede retains its traditional charm while gradually embracing modern developments. One of the livelihoods of the residents in Sambigede Village is farming, especially cattle and goats. Therefore, the need for grass for animal feed is increasing. One of the obstacles faced by the residents of Sambigede Village is the feed preparation time, especially during the grass-chopping process still uses the manual method. So if the grass takes a long time and energy. This problem can solve by using Appropriate Technology (TTG) for grass-chopping machines to help the role of residents in the grass-chopping process. It's hoped that after the grass-chopping machines, the residents of Sambigede Village can further improve the quality of livestock feed and increase the effectiveness of time during the grass-chopping process.